Normalization of Four Different Types of Pulmonary Hypertension After Atrial Septal Defect Closure - Rubáčková Popelová, Jana; Tomek, Jakub; Tomková, Markéta; Živná, Renata (Frontiers in Cardiovascular Medicine, 2022)
Pulmonary hypertension (PH) is an established risk factor in patients with atrial septal defect (ASD), and its persistence after ASD closure is associated with increased mortality. Therefore, predictors for PH normalization after defect closure are needed. Multiple hemodynamic types of PH exist, but little is known about their prevalence and prognostic value for PH normalization after ASD closure. We carried out a retrospective study on 97 patients (76% female, median age at ASD closure 58 years) with four types of PH determined predominantly by right heart catheterization: hyperkinetic, pulmonary arterial hypertension, isolated post-capillary, and combined pre- and post-capillary. We investigated the frequency of the PH types and their prognostic significance for PH normalization after ASD closure. Frequency of PH types before ASD closure in our study was: hyperkinetic 55%, pulmonary arterial hypertension 10%, isolated post-capillary PH 24%, and combined PH 11%. Hyperkinetic PH type was positively associated with PH normalization after ASD closure (78% patients normalized), remaining a significant independent predictor when adjusted for age at closure, sex, heart failure, and NYHA. Hyperkinetic PH patients also had significantly better survival prognosis versus patients with other PH types (p = 0.04). Combined PH was negatively associated with PH normalization, with no patients normalizing. Pulmonary arterial hypertension and isolated post-capillary PH had intermediate rates of normalization (60 and 52%, respectively). In summary, all four hemodynamic types of PH are found in adult patients with ASD, and they can be used to stratify patients by their likelihood of PH normalization and survival after ASD closure.